Sholat dalam bingkai syariat: kajian dalil, sejarah waktu, dan klasifikasi wajib–sunnah - SOFI, MUHAMAD (Maliki Interdisciplinary Journal, 2026)
English This study examines the position of prayer (Salah) in Islamic teachings by highlighting its meaning, the basis of its legislation (Sharia), the history of its prescribed times, and its classification from a Fiqh (Islamic jurisprudence) perspective. Prayer is understood as an act of worship that holds a special position as the primary means of spiritual communication between the servant and Allah SWT (God Almighty), which etymologically means supplication (dua) and blessings (salawat), while terminologically it is a form of servitude involving both physical and inner aspects through a structured series of recitations and movements. The study asserts that the obligation of prayer has been known since the time of previous prophets and was perfected through the event of Isra’ Mi’raj (the Night Journey and Ascension) in the form of the five daily prayers. The findings indicate that the legislation of prayer is based on solid arguments from the Qur’an and Hadith, while the determination of prayer times evolved from traditional observation of the sun’s movement towards scientific methods through calculation (hisab) and sighting (rukyat) in modern astronomy (ilm al-falak). Furthermore, prayers are divided into two major categories: obligatory (fardh) prayers and voluntary (sunnah) prayers, each having specific legal rulings, times, number of units (rak’ahs), and virtues in shaping individual discipline and piety. In conclusion, prayer is not only a ritual dimension but also contributes significantly to the formation of character, morality, and the quality of social life of Muslims. Therefore, a comprehensive understanding of the concept, legal basis, times, and types of prayer can improve the quality of its performance and spiritual experience in daily life.